(3NdGUI JMbjb GdXfhf aj GdTQhM hGdeJhfs - (3ceGd GdOjf GdHcQj , eMeO Hf eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj, ceGd GdOjf CHh GdaJhM,J (B1196 (3g` s ((3UGOb agei GdeGdM s)
(3ChdgG (B:s
(3HGH GdUGO GdegedI s
(3BNQgG (B:s
(3hHg Je eNJUQ cJGH cTa GdXfhf Yf CSeGA GdcJH hGdeJhf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B100 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B32s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B434s
Keywords: (3GdeYGQa GdYGeIs